The Role of Public Relations in Forming Positive Perception in Society - Mariyo Mariyo; Etika Khairina; Timbul Dompak; Lubna Salsabila (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to analyze and determine the relationship between good public relations management and the formation of positive perceptions in the community. Public relations is very important to pay attention to because public relations plays a strategic role in producing a good impression of government policies and programs as well as informing the public and fostering beneficial relationships between the government and society. This research uses a qualitative research method with a descriptive approach, where the main data is obtained through literature studies carried out on previous studies and journals and then analyzed in depth to draw conclusions. The findings in this research are that there is a close relationship between public relations activities and the formation of positive perceptions in society. Through effective communication, good image management, and mutually beneficial interactions, public relations has the potential to influence public perceptions by providing accurate information, maintaining a good reputation, and building relationships of mutual trust.